2016
DOI: 10.1017/s0025315416001557
|View full text |Cite
|
Sign up to set email alerts
|

Connecting pH with body size in the marine gastropod Trophon geversianus in a latitudinal gradient along the south-western Atlantic coast

Abstract: There is growing concern about the impact of contemporaneous ocean acidification on marine ecosystems, but strong evidence for predicting the consequences is still scant. We have used the gastropod Trophon geversianus as a study model for exploring the importance of oceanographic variables (sea surface temperature, chlorophyll a, oxygen, calcite and pH) on large-scale latitudinal variation in mean shell length and relative shell weight. Data were collected from a survey carried out in 34 sites along ~1600 km. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
9
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 47 publications
1
9
1
Order By: Relevance
“…This context reinforces the idea that local and regional scales are interrelated (Huston, 1999;Resetarits, 2005), and thus studying outlier sites may give us important insights into the local features of an area that can override the large-scale processes that drive regional grouping patterns (Blanchette et al, 2008). Moreover, throughout the geographic range of a species, the distinctiveness and peculiarity of particular sites may disrupt expected general patterns (e.g., ecogeographic rules) when considering multi-ple sites at a regional scale (Malvé et al, 2018a). Embracing a regional approach is therefore of paramount importance since studies that cover the entire geographic range of a species along the south-west Patagonian coast (from Río Negro Province to Tierra del Fuego) are scant, thus limiting our ability to answer basic biogeographic questions (Fenberg & Rivadeneira, 2011).…”
supporting
confidence: 68%
See 1 more Smart Citation
“…This context reinforces the idea that local and regional scales are interrelated (Huston, 1999;Resetarits, 2005), and thus studying outlier sites may give us important insights into the local features of an area that can override the large-scale processes that drive regional grouping patterns (Blanchette et al, 2008). Moreover, throughout the geographic range of a species, the distinctiveness and peculiarity of particular sites may disrupt expected general patterns (e.g., ecogeographic rules) when considering multi-ple sites at a regional scale (Malvé et al, 2018a). Embracing a regional approach is therefore of paramount importance since studies that cover the entire geographic range of a species along the south-west Patagonian coast (from Río Negro Province to Tierra del Fuego) are scant, thus limiting our ability to answer basic biogeographic questions (Fenberg & Rivadeneira, 2011).…”
supporting
confidence: 68%
“…In a recent study, Malvé et al (2018b) evaluated biogeographic shell shape variation in the marine snail Trophon geversianus, and recognized two morphotypes matching the biogeographic scheme of the Argentine Sea. In a previous study on the same species, Malvé et al (2018a) also found that neither shell length nor relative shell weight showed any monotonic latitudinal trend, and the patterns of spatial variability were rather complex. These authors recognized a weak, non-significant, tendency of body size increase towards the south, with extremely large individuals at the Magellan Strait and Beagle Channel (southern South America).…”
mentioning
confidence: 79%
“…The latitudinal increase in body size of co-specific populations has been tested in freshwater, terrestrial and marine animal groups (Blanckenhorn & Demont, 2004; Linse et al ., 2006; Angielczyk et al ., 2015; Malvé et al ., 2018). According to our hypothesis that size of the gastropods would increase according to the latitudinal gradient in our localities, results showed a moderately positive relationship between the size of the individuals and each latitude.…”
Section: Discussionmentioning
confidence: 99%
“…However, when the whole dataset was considered, the largest sized gastropod was not observed at the highest latitude (23°S in this study). The variability of body size has a complex spatial tendency that cannot be easily framed by ecogeographic rules such as Bergmann's rule (Malvé et al ., 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation